Peranan Internet dalam Meningkatkan Pendapatan Wirausaha Informal Bidang Jasa - Diroatmodjo, Indah Safira; Wardhana, Adhitya (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
Despite employing more than half of the national workforce, informal entrepreneurs in the service sector continue to earn less than their counterparts in the formal sector. This study aims to analyze informal entrepreneurship in the service sector, which is indicated to have the potential to improve local economies. The study uses 52,349 observations and applies the Ordinary Least Squares (OLS) method. Data were drawn from the 2019 National Labor Force Survey (Sakernas) and regional minimum wage (UMR) data published by Statistics Indonesia (BPS). The variables used in this study include internet usage, age, education level, gender, place of residence, work duration, weekly working hours, and UMR. The results indicate that internet usage has a positive and significant effect on income, with an estimated contribution of 29.1 percent. Other factors such as age, education, urban residence, work duration, working hours, and minimum wage are also significant. These findings highlight the importance of accelerating digitalization as a strategy to enhance the welfare of informal service entrepreneurs.